2008
DOI: 10.1074/jbc.m801637200
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Protein HMGB2 Is a Critical Regulator of Plasmodium Oocyst Development

Abstract: The sexual cycle of Plasmodium is required for transmission of malaria from mosquitoes to mammals, but how parasites induce the expression of genes required for the sexual stages is not known. We disrupted the Plasmodium yoelii gene encoding high mobility group nuclear factor hmgb2, which encodes a DNA-binding protein potentially implicated in transcriptional regulation of malaria gene expression. We investigated its function in vivo in the vertebrate and invertebrate hosts. ⌬pyhmgb2 parasites develop into gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…[55][56][57][58], and a similar mechanism may act here as well. Equally, high mobility group protein, a nuclear factor that is involved in the modification of histones, has been implicated in playing a role in the transcriptional control of gene expression in the sexual stage of P. yoelii, and it is important in oocyst development in the mosquito (59). Its up-regulation during invasion pathway switching is consistent with the epigenetic regulation of the RH4 locus.…”
Section: Discussionmentioning
confidence: 49%
“…[55][56][57][58], and a similar mechanism may act here as well. Equally, high mobility group protein, a nuclear factor that is involved in the modification of histones, has been implicated in playing a role in the transcriptional control of gene expression in the sexual stage of P. yoelii, and it is important in oocyst development in the mosquito (59). Its up-regulation during invasion pathway switching is consistent with the epigenetic regulation of the RH4 locus.…”
Section: Discussionmentioning
confidence: 49%
“…*, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001. and investigated their growth and their ability to drive ECM in C57BL/6 and BALB/c mice. Few studies have reported gene disruption at the level of erythrocytes in vivo (59)(60)(61). In mice, an absence of the hmgb1 gene is lethal, since hmgb1 Ϫ/Ϫ mice are not viable and die a few hours after birth (62).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, genome-wide bioinformatic predictions of AP2 domain recognition elements define multiple potential binding sites upstream of virtually all open reading frames [42]. Of course additional DNA binding proteins, some of which have already been identified such as Myb1 (PF13_0088) [63, 64], Myb2 (PF10_0327) [21] and the high mobility group (HMGB) proteins (MAL8P1.72 and PFL0145c) [65, 66], will contribute to the overall picture of transcriptional regulation. In summary, ApiAP2 proteins may function in protein complexes to regulate transcription, and the identification of such complexes will be a key step in unraveling transcription factor-based control of gene expression in Plasmodium .…”
Section: Plasmodium Apiap2 Proteins: Developmental Regulators?mentioning
confidence: 99%